Community priorities for obesity prevention among low-income adults in Kuala Lumpur: a discrete choice experiment. (11th November 2022) - Kocher, Erica; Wood, Dallas; Lim, Shiang-Cheng; Jackson-Morris, Angie; Kataria, Ishu; Ngongo, Carrie; Sham, Zhi; Chandran, Arunah; Nugent, Rachel; Mustapha, Feisul Idzwan
Summary: Non-communicable diseases and associated risk factors, such as obesity, are prevalent and increasing in Malaysia. To address this burden and the heightened vulnerability of low-income communities to these risk factors, the Better Health Programme Malaysia conducted a partial-profile discrete choice experiment (DCE) to inform the design of a community-based obesity-prevention programme. The DCE survey was conducted with community members ( n = 1453) from three publicly supported low-cost, high-rise flat complexes in urban Kuala Lumpur. In the survey, community members were asked to choose between different sets of potential evidence-based interventions for obesity prevention. Their responses to these choice tasks were analysed to quantify preferences for these different health interventions using a random utility maximization model. Based on these results, we determined participants' relative prioritization of the different options. The most preferred interventions were those that reduced the price of fruit and vegetables; altered cooking practices at restaurants and food vendors to reduce salt, sugar and oil; and offered reward incentives for completing online educational activities. Community members did not prioritize several evidence-based interventions, including changes to product placement or product labelling, suggesting that these effective approaches may be less familiar or simply not preferred by respondents. The DCE enabled the clear articulation of these community priorities for evidence-based interventions that focus on the supply and promotion of affordable healthy foods within the local food environment, as well as community demand for healthier food options. Lay Summary: Non-communicable diseases (NCDs) and the factors that increase NCD risk, such as obesity, are widespread and increasing in Malaysia. Low-income communities are particularly vulnerable to these risk factors. The Better Health Programme (BHP) Malaysia conducted a discrete choice experiment (DCE) to elicit community member preferences for evidence-based health promotion interventions to prevent obesity and NCDs. DCE is a research method used to identify participant preferences between different pre-determined options. The DCE survey was conducted with community members ( n = 1453) from three publicly supported low-cost, high-rise flat complexes in urban Kuala Lumpur. In the survey, community members were asked to choose between different potential sets of interventions to alter the environment to prevent obesity. Based on their responses, we determined which interventions were most preferred in each community. The most preferred interventions were those that reduced the price of fruit and vegetables; altered cooking practices at restaurants and food vendors to reduce salt, sugar and oil; and offered rewards for completing online educational activities. The survey enabled the clear articulation of these community priorities for evidence-based interventions. These priorities were used to design the BHP Malaysia intervention programme.